Вплив регіональних закономірностей будови вуглепородного масиву на формування техногенних скупчень метану в підробленій гірській товщі - Лукінов, В.В.; Приходченко, О.В.; Нагорний, Ю.М. (Геотехническая механика, 2012)
Выполнена оценка плотности остаточных ресурсов метана для шахт Донецко-
Макеевского геолого-промышленного района. Установлена тенденция увеличения плотности остаточных ресурсов метана в северо-восточном направлении. Estimation of remining resources of anthropogenic accumulations of methane for mines
Donetsko-Makeevsk region has been performed. A trend of increasing density of residual methane resources in the north-east at Donetsko-Makeevsk region had been found. Increase the density of residual resources of methane from coal-bearing strata capacity increase had been proved.